Influence of seeding density on seed and oil yield, and fatty acid composition of white mustard (Sinapis alba L.) - Brcić, Marina (Acta agriculturae Slovenica, 2024)
The aim of this study was to determine the effects of seeding density on the seed yield of white mustard, the oil yield and fatty acid composition under the agroecological conditions of the northwestern Republic of Croatia. The field trials were conducted at the experimental station of the Faculty of Agriculture, University of Zagreb (45° 48’ N, 16° 05’ E) during two growing seasons. The trial included four seeding densi-ties of white mustard: 50, 70, 90 and 110 germinable seeds m-2. The trial was set up using a randomized block design with five replications. The highest seed yield was obtained with a seeding density of 110 germinable seeds m-2, with no significant differences between seeding rates of 70 and 90 germinable seeds m-2. The average oil content during researched years varied from 23.97 % in the seeding density of 50 germinable seeds m-2 to 24.37 % in the seeding density of 90 germinable seeds m-2. The higher oil yield was achieved in 2014 due to the higher oil content in the seed that year. Regarding fatty acid composition, erucic acid was dominant along with oleic acid, linoleic acid, and linolenic acid
Keywords: alternative oilseeds; biodisel; biodizel; erucic acid; gorjušica; lubricants; mustard; oil content; vsebnost olja